A multigenerational family with multiple sclerosis. - Dyment, D; Cader, M; Willer, C; Risch, N; Sadovnick, A; Ebers, G (2002)
We report a family with 15 individuals affected with multiple sclerosis present in three and possibly four generations. The segregation of multiple sclerosis within this pedigree is consistent with an autosomal dominant mode of inheritance with reduced penetrance. The clinical characteristics of the affected individuals are indistinguishable from those seen in sporadic multiple sclerosis with respect to sex ratio, age at onset, onset symptom, MRI and clinical course. Eleven of 14 cases (78.6%) were positive for the known multiple sclerosis-associated major histocompatibility complex (MHC) Class II HLA DRB1*15 allele. Parametric linkage analysis gave a non-significant LOD score of 0.31 (theta; = 0.33) for the DRB1 gene. However, among 11 affected children with at least one DRB1*15 bearing parent, all 11 out of 11 received at least one copy of this known susceptibility allele. A transmission disequilibrium test analysis was significant for the DRB1*15 allele within this single family; P = 0.0054. The inheritance pattern in this family suggests the presence of a single major locus responsible for multiple sclerosis susceptibility, with DRB1 acting as an important modifier. This family could be an important resource for the identification of a multiple sclerosis susceptibility gene.